Bentuk Kalimat Amr dalam Al-Qur'an - mariyono (Kopertais Wilayah III Yogyakarta, 2022)
This writing discusses about Style of Authority or Amr in Holy Quran. The articulation of Amr in language means authority that in general is from superiority to subordinate, say, from a father to a child. In essence, Amr (authority) contains three meanings in accordance to the Ulama. Asy-‘ari, Al-Ghazali defined it as the articulations showing the demand to the ones demanded as what is demanded. Ahnaf and ar-Razi stated that the meaning of amr means to demand for an action to the higher level and as defined by Abdul Wahab Al-Maliki, amr means calling for a deed from the higher level. Meanwhile, arm or demand consists of four forms: First, Fi’il amr (verb consisting of three letters), rubai (verb consisting of four letters), khumasi (verb consisting of five letters) and sudasi (verb consisting of six letters) Wab taghu ilaihi Al-Wasilata. Second Fi’il mudhari’ al muqtarin bi lam al-amr (Fi’il mudhari preceded, lam demand), example : Wal yakhsya Al-ladzina la taraku min khalfihim. Third, isim Fi’il amr (isim fu’il amr), example : alaikumusiyam. Fourth, masdhar an-naib ‘an fi’il al-amr (form of masdar replacing the form of fi’il amr), example : wabil walidaini ihsana (and to parents, you should do the good deeds).keywords: kalimat, Amr, al-Qur’an.